Creative Leadership of School Administrators Affecting the Quality of Teachers' Performance under the Kamphaeng Phet Primary Educational Service Area Office 1 - Phuengarsa, Pichet; Nakai, Nikom (Academic MCU Buriram Journal, 2025)
The purposes of this research were: 1) to study level of the creative leadership of school administrators, 2) to study level of the quality of teachers' performance, 3) to study the relationship between creative leadership of school administrators and the quality of teachers' performance, and 4) to examine the creative leadership of school administrators that affected the quality of teachers' performance under the Kamphaeng Phet Primary Educational Service Area Office 1. The samples of this study were 136 schools under the Kamphaeng Phet Primary Educational Service Area Office 1, Determined the sample size from the opening of the ready-made tables of Krejcie & Morgan. The data providers were 136 school administrators and 136 teachers. The instruments was a questionnaire of 36 topics with separated 3 parts. The statistics used were mean, standard deviation, Pearson Correlation, Coefficient and Enter Multiple Regression Analysis. The research results found that: 1) the overall creative leadership of school administrators were at a high level 2) the quality of teachers' performance were at a high level 3) the relationship between creative leadership of school administrators and the quality of teachers' performance in overall was positive and was in quite high level with the statistical significance at the .01 level and 4) creative leaderships of 4 school administrators were able to predict the quality of teachers' performance under the Kamphaeng Phet Primary Educational Service Area Office 1 at 78.6 percent. The prediction equation in the form of raw score indicated the Mean_Vtotal = .702 + 0.097Xa_total + 0.993Xb_total + 0.001Xc_total - 0.244Xd_total, and the prediction equation in the form of standard score showed ZMean_Vtotal = 0.120ZXa_total + 1.031ZXb_total + 0.001ZXc_total - 0.270ZXd_total